THE DOMINANCE OF FATHER'S ROLE IN THE FILM NGERI-NGERI SEDAP - Aryati, Putri; Adiprabowo, Vani Dias (Institut Seni Indonesia Yogyakarta, 2023)
The purpose of this research is to identify the pattern of family communication in the film